INCREASING KNOWLEDGE ABOUT COVID-19 VACCINATION IN THE COMMUNITY THROUGH THE PRODOMAT WEBINAR - Yanasta Yudo Pratama; Trismadani Erlina Putri; Sri Wahyunita Mohamad; Rissa Widyasworo Hartanti; Sunarti Sunarti; Solikhah Solikhah (Jurnal Pengabdian Masyarakat Dalam Kesehatan, 2022)
Introduction: The COVID-19 pandemic has become an issue that has been in the world's spotlight in the last 2 years. The high mortality and morbidity rates have caused the world to work hand in hand to control the spread of COVID-19. This webinar is expected to increase knowledge in the community so that later it can help the Government and Health Workers in efforts to control the spread of COVID-19. Methods: This webinar was held in 1 day with 2 resource persons who are experts in their fields. This webinar uses the Zoom Webinar facility from the UAD Faculty of Public Health. The target of this webinar was the general public, both students and non-students. In the webinar session, there were pretest and posttest which are distributed online using a Google Form questionnaire. The analysis used a descriptive analysis of the characteristics of webinar participants. Results: There were 50 participants in this webinar with different job characteristics and educational backgrounds. More than half of the total participants already had knowledge of COVID-19 vaccination and mostly participants had increased knowledge seen from the posttest results. The result of post test are 84.6%, 48.7%, 100%, 100%, 100%, 87%, 84%, 87%, 87% in the first until nine questions. Conclusion: Webinar by zoom could increase knowledge about COVID-19 vaccination. This webinar still uses a small participant, and should be increased to a larger by promoting similar webinars in advance or with more platforms.